Bacterial Artificial Chromosomes Volume 2: Functional Studies - Zhao, Shaying; Stodolsky, Marvin; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
The ability to transfer and maintain DNA both within and between species is an essential skill in biotechnology and medicine. In Bacterial Artificial Chromosomes, expert investigators describe not only the classic methods, but also the many novel techniques they have perfected for the transfer of large DNAs into the cells of both microbes and animals via large-insert recombinant DNAs. Volume 2: Functional Studies provides a wide variety of methods and applications for functional analysis of the DNA-transformed organisms. The laboratory protocols follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Besides protocols, each chapter includes scientific reviews, software tools, database resources, genome sequencing strategies, and illustrative case studies. An accompanying volume, Volume 1: Library Construction, Physical Mapping, and Sequencing, presents readily reproducible techniques for library construction, physical mapping, and sequencing. Comprehensive and cutting-edge, the two volumes of Bacterial Artificial Chromosomes provide a superlative collection of highly productive protocols that will prove useful to many bioscientists, including genome sequencers, geneticists, molecular biologists, and biochemists studying the structure and function of specific genomes.
Use of BAC End Sequences for SNP Discovery -- Exon Trapping for Positional Cloning and Fingerprinting -- Isolation of CpG Islands From BAC Clones Using a Methyl-CpG Binding Column -- BAC Microarray-Based Comparative Genomic Hybridization -- Large DNA Transformation in Plants -- Retrofitting BACs With a Selectable Marker for Transfection -- BAC Modification Using a RecA Expressing Shuttle Vector System -- Bacterial Artificial Chromosome Engineering -- ET Recombination -- BAC Engineering for the Generation of ES Cell-Targeting Constructs and Mouse Transgenes -- Microinjection of BAC DNA into the Pronuclei of Fertilized Mouse Oocytes -- Generation of BAC Transgenic Mice -- BAC Rescue -- Herpesviruses -- Cloning of ?-Herpesvirus Genomes as Bacterial Artificial Chromosomes -- Construction of HSV-1 BACs and Their Use for Packaging of HSV-1-Based Amplicon Vectors -- Mutagenesis of Viral BACs With Linear PCR Fragments (ET Recombination) -- Mutagenesis of Herpesvirus BACs by Allele Replacement -- Herpesvirus Genome Mutagenesis by Transposon-Mediated Strategies -- Protective DNA Vaccination by Particle Bombardment Using BAC DNA Containing a Replication-Competent, Packaging-Defective Genome of Herpes Simplex Virus Type I.
Keywords: Microbiology; Microbiology